Deep Brain Stimulation for Parkinson’s Disease During the COVID-19 Pandemic: Patient Perspective - Zhang, Chencheng; Zhang, Jing; Qiu, Xian; Zhang, Yingying; Lin, Zhengyu; Huang, Peng; Pan, Yixin; Storch, Eric A.; Sun, Bomin; Li, Dianyou (Frontiers in Human Neuroscience, 2021)
Background: Public health guidelines have recommended that elective medical procedures, including deep brain stimulation (DBS) surgery for Parkinson's disease (PD), should not be scheduled during the coronavirus (COVID-19) pandemic to prevent further virus spread and overload on health care systems. However, delaying DBS surgery for PD may not be in the best interest of individual patients and is not called for in regions where virus spread is under control and inpatient facilities are not overloaded. Methods: We administered a newly developed phone questionnaire to 20 consecutive patients with PD who received DBS surgery in Ruijin Hospital in Shanghai during the COVID-19 pandemic. The questionnaire was designed to gather the patients’ experiences and perceptions on the impact of COVID-19 on their everyday activities and access to medical care. Results: Most of the patients felt confident about the preventive measures taken by the government and hospitals, and they have changed their daily living activities accordingly. Moreover, a large majority of patients felt confident obtaining access to regular and COVID-19-related health care services if needed. Routine clinical referral, sense of security in the hospital during the outbreak, and poor control of PD symptoms were the three main reasons given by patients for seeking DBS surgery during the COVID-19 pandemic. Conclusions: The COVID-19 pandemic has considerably impacted medical care and patients’ lives but elective procedures, such as DBS surgery for PD, do not need to be rescheduled when the health care system is not overloaded and adequate public health regulations are in place.